Utilizing magnetic resonance techniques to study membrane interactions of amyloid peptides. (30th June 2021) - Rajput, Sunnia; Sani, Marc-Antoine; Keizer, David W.; Separovic, Frances
Abstract : Alzheimer's disease (AD) is a common neurodegenerative condition that involves the extracellular accumulation of amyloid plaques predominantly consisting of Aβ peptide aggregates. The amyloid plaques and soluble oligomeric species of Aβ are believed to be the major cause of synaptic dysfunction in AD brain and their cytotoxic mechanisms have been proposed to involve interactions with cell membranes. In this review, we discuss our solid-state nuclear magnetic resonance (ssNMR) studies of Aβ interactions with model membranes.